Do government-funded patents have higher quality than privately-funded patents?. Issue 4 (19th May 2023) - Choi, Jin-Uk; Lee, Chang-Yang
ABSTRACT: This paper examines whether there exists a quality difference between government-funded and privately-funded patents. Furthermore, to the extent that there is a quality difference, this paper investigates under what conditions such a difference is particularly more pronounced. Using a unique dataset of Korean manufacturing firms during the period of 2006-2010 that provides project-level information on public R&D subsidies, we find the following. First, for the pooled sample of patents, there exists a quality difference between government-funded and privately-funded patents. Overall, the quality of government-funded patents is higher than that of privately-funded ones. Second, within each firm, quality differences between government-funded and privately-funded patents are more likely to be positive for large firms than small ones. Third, within-firm quality differences between government-funded and privately-funded patents are more likely to be positive for firms with a large technological knowledge base, particularly when they perform more exploratory, rather than exploitative, R&D projects with public R&D subsidies.